Integrated Fabrication-Conjugation Approaches for Biomolecular Assembly and Protein Sensing with Biopolymeric-Synthetic Hydrogel Microparticle Platforms and Bioorthogonal Reactions. - Jung, Sukwon. (2017)
Abstract: Hydrogel microparticles have gained increasing attention as biosensing platforms due to the advantages of hydrogels and particle-based suspension arrays. In this dissertation, I examine facile fabrication‒conjugation approaches to construct hydrogel microparticle platforms that can be utilized for biosensing. Specifically, I exploit simple micromolding techniques for fabrication of highly uniform and chemically functional biopolymeric-synthetic hydrogel microparticles, and high yield bioorthogonal conjugation reactions for biomolecule conjugation with the as-prepared microparticles. Two novel approaches allowing for enhanced conjugation capacity and kinetics as well as sensing capability of the microparticle platforms are also examined in this dissertation. First, facile replica molding (RM) technique is employed to fabricate chitosan‒poly(ethylene glycol) (PEG) hydrogel microparticle platforms. The results show that highly uniform and well-defined chitosan‒PEG microparticles are readily fabricated via RM. Fluorescence labeling and FTIR microscopy results indicate stable incorporation of chitosan moieties with PEG networks in the microparticles while retaining their chemical reactivity toward amine-reactive chemistries. The utility of these microparticles as biomolecule conjugation platforms is then investigated via conjugation of model biomolecules such as fluorescein-labeled single-stranded (ss) DNAs and red fluorescent proteins (R-phycoerythrin, R-PE) via strain-promoted alkyne‒azide cycloaddition (SPAAC) reaction. Fluorescence and confocal microscopy results show highly selective conjugation of biomolecules near the particle surfaces under mild conditions as well as long-term stability of the conjugation scheme using SPAAC reaction. In-depth examination of R-PE conjugation kinetics with the microparticles shows multiple reaction regimes (i.e. rapid initial, intermediate, and steady final stage) owing to steric hindrance arising from the as-conjugated R-PEs and small mesh size of the microparticles. Next, the chitosan‒PEG microparticles are enlisted for target protein (R-PE) capture upon anti-R-PE antibody conjugation via SPAAC reaction, and the results show selective and rapid target protein capture with the antibody-conjugated microparticles. Next, I enlist viral nanotemplates to improve the hindered environment of the chitosan‒PEG microparticles, and thus their protein conjugation and kinetics as well as sensing capability. Specifically, tobacco mosaic virus (TMV) templates are assembled with the chitosan‒PEG microparticles via nucleic acid hybridization in order to provide abundant conjugation sites with minimal steric hindrance near the particle surfaces. R-PE conjugation results show significantly enhanced protein conjugation capacity of TMV assembled microparticles (TMV-particles) compared to planar substrates and the chitosan‒PEG microparticles. In-depth examination of protein conjugation kinetics via SPAAC and tetrazine‒trans-cyclooctene (Tz‒TCO) cycloaddition reaction indicates that the TMV-particles offer less hindered protein conjugation environment over the chitosan‒PEG microparticles. Target protein capture results with antibody conjugated TMV-particles also show substantially enhanced capture capacity over the antibody conjugated chitosan‒PEG microparticles. In addition, protein and antibody conjugation capacity are readily controlled by simply varying TMV concentrations, with negligible negative impact of densely assembled TMVs on the protein conjugation and capture capability. Lastly, I examine a simple and robust micromolding-based technique utilizing surface tension-induced droplet formation and polymerization-induced phase separation that allows for fabrication of monodisperse chitosan‒PEG microspheres with macroporous and/or intriguing core-shell structures. The utility of these microspheres as platforms for biomolecule conjugation is then thoroughly examined via conjugation of the model biomolecules via SPAAC and Tz-TCO reaction. The results show not only programmable protein conjugation but also enhanced conjugation capacity and kinetics rising from the controlled macroporous structures. Overall, the results described in this dissertation illustrate facile fabrication‒conjugation approaches for construction of biosensing platforms via simple micromolding techniques and efficient bioorthogonal conjugation reactions. I expect that these approaches can be readily enlisted in a wide range of biosensing application areas such as medical diagnostics, bioprocess monitoring, and pathogen detection for biodefense.; Thesis (Ph.D.)--Tufts University, 2015.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisor: Hyunmin Yi.; Committee: Asatekin Ayse, Qiaobing Xu, and Chang-Soo Lee.; Keyword: Chemical engineering.